2016
DOI: 10.1159/000447059
|View full text |Cite
|
Sign up to set email alerts
|

Escalation Therapy of Steroid Refractory Multiple Sclerosis Relapse with Tryptophan Immunoadsorption - Observational Multicenter Study with 147 Patients

Abstract: Background: A marked proportion of multiple sclerosis (MS) relapses is followed by incomplete recovery. Our aim was to considerably increase the evidence of the clinical use of immunoadsorption (IA) as escalation therapy for patients with MS relapse. Methods: A retrospective multicenter study was performed in MS patients with steroid refractory relapse who were treated with tryptophan IA. The main outcome parameter was change of acute relapse-related disability assessed by Expanded Disability Status Scale (EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…In recent studies in nonpregnant patients, tryptophan IA reduced the level of disability and was well tolerated as second-line therapy for MS and NMOSD relapses. 24 28 , 30 , 31 These studies and the given risks of high steroid doses have been our rationale for also applying IA in pregnant and breastfeeding patients. We observed functional improvement of acute relapse-related symptoms in 83% (20/24) of patients shortly after the IA series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies in nonpregnant patients, tryptophan IA reduced the level of disability and was well tolerated as second-line therapy for MS and NMOSD relapses. 24 28 , 30 , 31 These studies and the given risks of high steroid doses have been our rationale for also applying IA in pregnant and breastfeeding patients. We observed functional improvement of acute relapse-related symptoms in 83% (20/24) of patients shortly after the IA series.…”
Section: Discussionmentioning
confidence: 99%
“… 20 23 Recent studies evaluating the efficacy and tolerability of tryptophan IA as second-line therapy for MS relapses after one or more steroid pulses show response rates between 70% and almost 90% in more than 200 patients. 24 28 In the largest study with 147 patients, good tolerability of tryptophan IA was reported in 98.9% of treatments. 27 But only little is known on the use, efficiency and safety of PE or IA during pregnancy or breastfeeding in patients with MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die TA stellt in diesem Zusammenhang einen wichtigen therapeutischen Ansatz dar, wobei sich die IA als effektive Therapieoption herausgestellt. Retrospektive Studien zeigen eine vergleichbare Effektivität der IA im Vergleich zum TPA [29,30]. Insbesondere im Bereich der therapierefraktären MS besteht auch im Rahmen nationaler und internationaler Leitlinien die Empfehlung der Durchführung einer PP oder einer IA [24,31].…”
Section: Bereichunclassified
“…There is an increasing body of evidence that selective immunoadsorption (IA) is at least equivalent to conventional PE with respect to clinical efficacy in autoimmune neurological diseases, such as multiple sclerosis, myasthenia gravis, or Guillain–Barré syndrome . In contrast to PE, IA uses an immunosorbent to selectively remove immunoglobulins (IgG and IgM) and immune complexes from the plasma by hydrophobic and ionic interactions with the adsorber surface.…”
Section: Introductionmentioning
confidence: 99%